2008
DOI: 10.4314/ari.v1i1.40732
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <i>Fasciola gigantica, Cysticercus bovis</i> and some other disease conditions of cattle slaughtered in Nsukka urban abattoir

Abstract: The prevalence of some parasitic infections and other disease conditions of cattle slaughtered in Nsukka urban abattoir was studied from November to December 2001. The tongues, hearts, masseter muscles, intercostal muscles, lungs, spleens, and livers o cattle were examined for various parasitic infections and disease conditions. The examinations were done by dissection, palpation and other physical procedures. Of the organs examined, the lungs, spleen, and liver were infected. The only case of Cysticercus bovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…This prevalence is of concern considering the public health importance of this zoonotic metacestode in causing ocular and neurocysticercosis and the growing recognition of its involvement in epilepsy in sub-Saharan Africa (Diop et al, 2003). The higher infection rate recorded by females than the males is in agreement with the report of Ngwu et al (2004). The higher infection rate observed in females may be attributed to stress associated with hormonal in-balances during pregnancy thus increasing their risk to the infection.…”
Section: Discussionsupporting
confidence: 74%
“…This prevalence is of concern considering the public health importance of this zoonotic metacestode in causing ocular and neurocysticercosis and the growing recognition of its involvement in epilepsy in sub-Saharan Africa (Diop et al, 2003). The higher infection rate recorded by females than the males is in agreement with the report of Ngwu et al (2004). The higher infection rate observed in females may be attributed to stress associated with hormonal in-balances during pregnancy thus increasing their risk to the infection.…”
Section: Discussionsupporting
confidence: 74%
“…This agreed with Elkhtam et al (2016) reported 6.09% in Menofia Governorate, as well as abroad in Brazil, (Almeida et al, 2002), Vietnam (Van De et al, 2014 in 23 European countries (Laranjo-González et al, 2016), and in Ethiopia (Engdaw et al, 2015;Wondimagegnei and Belete, 2015;Jemal and Kebede, 2016), however, Dada (1980) reported 0.9% in Sudan. These data were higher than that 2.16% in Zimbabwe (Pugh and chambers, 1989;Phiri, 2006) in Zambia and by Abu-Elwafa andAl-Araby (2008), Basem et al (2009) in Egypt, Ofukwu et al (2009), Rabi'u and Jegede (2010), Ngwu et al (2004) in Nigeria, Kozłowska-Łój (2012) in Poland, Dupuy et al (2014) in France, Dorny et al (2009) in Belgium and Rossi et al (2016) in Brazil. On the contrary, the present data was lower than (20%), reported by Abdel-Hafeez et al (2015) in Egypt, Mosienyane (1986) in Botswana, Kebede (2008), andAbunna et al (2008) in Ethio-pia.…”
Section: Resultsmentioning
confidence: 72%
“…The prevalence distribution of bovine fasciolosis is mapped (fig. 1) according to available data published between 1980 and 2016 (Schillhorn van Veen, 1980, Nwosu & Srivastava, 1993; Ngwu et al, 2004; Opara, 2005; Ekwunife & Eneanya, 2006; Adedokun et al, 2008; Umar et al, 2009; Ibironke & Fasina, 2010; Sugun et al, 2010; Gboeloh, 2012; Omoleye, 2012; Odigie & Odigie, 2013; Abraham & Jude, 2014; Ardo et al ., 2014; Magaji et al , 2014; Ngele & Ibe, 2014; Onyeabor, 2014; Yahaya & Tyav, 2014; Ejeh et al, 2015; Elelu et al, 2016). The high prevalence rate from liver condemnation in a 3-year period reported in Lagos State (Ibironke & Fasina, 2010) can be explained by the fact that this State is the commercial nerve centre of Nigeria, with a very large human population, and many cattle from all over the country are often slaughtered at the abattoir.…”
Section: Epidemiology Of Bovine Fasciolosis In Nigeriamentioning
confidence: 99%